Implementing Storytelling Method in Teaching English to Primary School Students - Rostina Rostina; Dien Afni Ariyati; Sri Hariati Mustari (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Storytelling has been widely recognized as an effective method for teaching English to young learners because it presents language in meaningful and engaging contexts. This study aims to explore the implementation of storytelling in teaching English to primary school students and to examine the perceived benefits and challenges from the teacher’s perspective. The study employed a qualitative descriptive research design involving one English teacher who taught Grade 6 students at SDN 261 Pinrang. The participant was selected through purposive sampling due to her experience in applying storytelling activities in English instruction at the lower primary level. Data were collected through a semi-structured interview and documentation, including lesson plans and teaching materials related to storytelling used in the classroom. The data were analyzed using descriptive qualitative analysis by identifying recurring themes related to classroom implementation, student responses, perceived benefits, and instructional challenges. The findings reveal that storytelling was mainly implemented in listening and speaking activities using simple and familiar stories, visual aids, and follow-up tasks such as comprehension questions and story retelling. According to the teacher, storytelling contributed positively to students’ listening skills, vocabulary acquisition, motivation, and confidence in using English. Students showed higher levels of attention, engagement, and willingness to participate during storytelling sessions compared to traditional teaching methods. However, several challenges were also identified, including difficulty in selecting age-appropriate and culturally relevant stories, limited instructional time, large class size, and the teacher’s need for further training in designing effective storytelling activities. Despite these challenges, the study concludes that storytelling can create a positive and supportive learning environment when it is carefully planned and supported by adequate teacher preparation. The findings highlight the importance of instructional support to maximize the effectiveness of storytelling in primary EFL classrooms.